Gastrodia motuoensis (Orchidaceae, Epidendroideae), a new species of mycoheterotrophic plant from Xizang, China, based on morphological and molecular evidence - Wang, Hanchen; Jin, Xiaohua (Phytotaxa, 2025)
Gastrodia motuoensis, a new species of mycoheterotrophic orchid from Southeast Xizang, China, is described and illustrated. Morphologically the new species allies with G. theana, G. sikkimensis, G. albida, and G. nipponica in their dwarf stature, not widely opening flowers, and lateral wings of the column, but it is distinct in its larger petals, lip with shortly caudate apex, a pair of lamellae on disc, and the stigma positioned at the middle of the column. Results of molecular phylogenetics based on plastid protein-coding sequences reveal that the new species is sister to G. crispa + G. flexistyla with high support, all of which belong to a recently diverged clade inside the genus Gastrodia. The discovery of G. motuoensis, together with several other Gastrodia species described in recent years, highlights potentially underrecognized diversity of these cryptic mycoheterotrophs.